Skin Care Routine among Female Medical Students at Qassim University, Qassim, Saudi Arabia - Alotaibi, Moteb; Alshammari, Asmaa Buraykan; Alotaibi, Ola Abdullah; ALkhyari, Meead Hamad; Himaid, Amjad Saad; Altabib, Atheer Mohammed; Alsoraya, Bayan Mohammed; Alkhudair, Maha Abdullah (International Journal of Innovative Research in Medical Science, 2019)
Background: A gap exists when measuring skin routine care among females, generally in Saudi Arabia. Accordingly, measuring skincare routine practicing among female medical students will provide the community with the needed information that will help in enhancing skincare results and increase awareness of its importance. Method: A cross-sectional study held at Qassim University. The data was collected through a self-administrated questionnaire. The data was entered and analyzed using Statistical Package for Social Science (SPSS) version 22. Results: The total sample size reached 218 female medical students, of whom 99.1% were Saudi (216). Moreover, 55.5% have a combination skin type, while 16.1% have oily skin. The brand comes on the top of the factors determining the students' choices of skincare products while friend's recommendation came in second place. There is an insignificant relationship between age and factors determining the students' decision to buy a skincare product and between skin type and factors. Forty four percent have reactions to some skin products, and there is an insignificant relationship between age and reactions to skin products and between skin type and reactions. There is an insignificant relationship between age and skincare routines and between skin type and skincare routines. Unfortunately, 46.8% never consulted a dermatologist before choosing skin products. Conclusion: The majority of skincare routines do not depend on medical consultancy. This indicates the need to increase the awareness of students to consult dermatologists, in order to avoid the high rate of reactions to some products.